DD-009 Evaluation of a frozen logistics circuit implementation. (14th February 2016) - Danet, C; Leclère, A; Desplechain, M; Mouls, M; Vitale, G; Beaugrand, N
Abstract : Background: A new haemostatic specialty, Tisseel (fibrin sealant), has replaced Tissucol. According to the Summary of Product Characteristics (SPC), Tisseel must meet special storage conditions – frozen product at or below -20°C, without any possible temperature fluctuations. These conditions require the establishment of a secure frozen circuit in our pharmacy and a logistics platform, located remotely from the healthcare services. Purpose: To determine the implementation modalities of a frozen logistics circuit from receipt to delivery of drugs in the healthcare service. To estimate the needs and necessary costs for the establishment of such a circuit. Material and methods: A retrospective analysis was conducted from January 2015 to July 2015. In order to evaluate storage and transportation needs, we estimated the stock for Tisseel from Tissucol data based on three dosages (average stock). We thus evaluated our storage volume in the freezer. We extracted consumption from the warehouse management system Copilote. We determined the number of consumer services and the average number of shipments. We were then able to assess the number and capacity of coolers necessary for delivery to healthcare services. Results: The volume required for storage of three dosages of Tisseel was estimated at 82 litres. Coolers offered by the laboratory are not suitable for our logistics circuit because of our delivery time (3 h maximum). We then evaluated purchase of new coolers with eutectic plates guaranteeing transport at -20°C for 3 h. Every week, about 17 coolers with a capacity of 3.5 litres will be needed to transport Tisseel from the platform to the consumer services. This purchase represents an additional cost of €4488. If products are not stored in the pharmacy (off-stock circuit), buying 10 pairs of cryogenic gloves is necessary and this represents an extra cost of €1979. Conclusion: Tisseel cannot withstand temperature fluctuations, which represents a significant additional cost for our hospital, if it is stored in our pharmacy. To secure the circuit of frozen products, we have decided to focus on off-stock circuits that incur a smaller cost. Each service will place an order with the supplier. We will then carry out the delivery of medicines, using the delivery container of the laboratory with dry ice. No conflict of interest.